Neonatologist staffing is related to the inter-hospital variation of risk-adjusted mortality of very low birth weight infants in Korea - Myung Hee Lee; Jang Hoon Lee; Yun Sil Chang (Scientific Reports, 2024)
Abstract This study investigated whether hospital factors, including patient volume, unit level, and neonatologist staffing, were associated with variations in standardized mortality ratios (SMR) adjusted for patient factors in very-low-birth-weight infants (VLBWIs). A total of 15,766 VLBWIs born in 63 hospitals between 2013 and 2020 were analyzed using data from the Korean Neonatal Network cohort. SMRs were evaluated after adjusting for patient factors. High and low SMR groups were defined as hospitals outside the 95% confidence limits on the SMR funnel plot. The mortality rate of VLBWIs was 12.7%. The average case-mix SMR was 1.1; calculated by adjusting for six significant patient factors: antenatal steroid, gestational age, birth weight, sex, 5-min Apgar score, and congenital anomalies. Hospital factors of the low SMR group (N = 10) had higher unit levels, more annual volumes of VLBWIs, more number of neonatologists, and fewer neonatal intensive care beds per neonatologist than the high SMR group (N = 13). Multi-level risk adjustment revealed that only the number of neonatologists showed a significant fixed-effect on mortality besides fixed patient risk effect and a random hospital effect. Adjusting for the number of neonatologists decreased the variance partition coefficient and random-effects variance between hospitals by 11.36%. The number of neonatologists was independently associated with center-to-center differences in VLBWI mortality in Korea after adjustment for patient risks and hospital factors.